Progress and Perspective of Ceramic/Polymer Composite Solid Electrolytes for Lithium Batteries - Li, Song; Zhang, Shi‐Qi; Shen, Lu; Liu, Qi; Ma, Jia‐Bin; Lv, Wei; He, Yan‐Bing; Yang, Quan‐Hong (Advanced science, 2020)
Solid composite electrolytes (SCEs) that combine the advantages of solid polymer electrolytes (SPEs) and inorganic ceramic electrolytes (ICEs) present acceptable ionic conductivity, high mechanical strength, and favorable interfacial contact with electrodes, which greatly improve the electrochemical performance of all‐solid‐state batteries compared to single SPEs and ICEs. However, there are many challenges to overcome before the practical application of SCEs, including the low ionic conductivity less than 10−3 S cm−1 at ambient temperature, poor interfacial stability, and high interfacial resistance, which greatly restrict the room temperature performance. Herein, the advances of SCEs applied in all‐solid‐state lithium batteries are presented, including the Li ion migration mechanism of SCEs, the strategies to enhance the ionic conductivity of SCEs by various morphologies of ICEs, and construction methods of the low resistance and stable interfaces of SCEs with both cathode and anode. Finally, some typical applications of SCEs in lithium batteries are summarized and future development directions are prospected. This work presents how it is quite significant to further enhance the ionic conductivity of SCEs by developing the novel SPEs with the special morphology of ICEs for advanced all‐solid‐state lithium batteries. Herein, the advantages and ionic transport mechanisms of solid composite electrolyte (SCE) as well as the relationship between morphology of ceramic fillers and ionic conductivity of SCE are reviewed. Recent progress and strategies to settle interfacial issues for high‐performance all‐solid‐state lithium metal batteries with SCE are also concluded and future research directions of SCEs are proposed.